2020
DOI: 10.1080/13416979.2020.1744231
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and elevational patterns of masting across multiple species in a steep montane landscape from the perspective of forest mammal management

Abstract: Masting of trees affects the activity of large mammals that feed on their fruits, but the spatial patterns of masting at the scale of mammal home ranges across multiple tree species have rarely been investigated. Furthermore, the effects of elevation, which may affect site productivity and thereby alter temporal patterns of masting, have often been ignored. We investigated fruit production by 403 trees of six species that are preferred by Asian black bears over 10 years within a 30 × 30-km 2 landscape at 700-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Thus, the lack of studies related to flower masting along altitudinal gradients is not surprising. This is in contrast to seed masting, where changes of temporal patterns of masting were inter alia already linked to the variation in climatic conditions along elevational gradients (Masaki et al 2020 ). The authors found that mean fruiting density and fruiting frequency of Quercus crispula decreased with elevation, while the annual variation in fruiting density increased.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the lack of studies related to flower masting along altitudinal gradients is not surprising. This is in contrast to seed masting, where changes of temporal patterns of masting were inter alia already linked to the variation in climatic conditions along elevational gradients (Masaki et al 2020 ). The authors found that mean fruiting density and fruiting frequency of Quercus crispula decreased with elevation, while the annual variation in fruiting density increased.…”
Section: Discussionmentioning
confidence: 96%
“…To evaluate the potential effects of mast failures on dispersal distances, we have carried out analyses (i) including all individuals and (ii) excluding individuals that were sampled during autumn of poor mast years which may have been captured or removed far from their home range. Therefore, for the second analysis we excluded mother–offspring pairs in which the mother or offspring was captured or removed during autumn (from September to November) of the poor hard mast years 2006, 2008, 2010, 2012, 2014, 2016, and 2018 ( Kozakai et al 2011 ; Gunma Prefecture 2018 ; Masaki et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…During autumn, the production of hard mast, bears' dominant food item ( Q. crispula ) in this region shows great variation from year to year and that distinctive fluctuation shows high spatial synchrony over large areas (Kozakai et al, 2011). A survey on hard mast productivity between 2006 and 2015 was performed based on masting tree samples from 85 sites (sampling trees: n = 217.5 ± 74.8) (Kozakai et al, 2013; Masaki et al, 2020). The results from that survey were used in the present study to classify the monitored years into two categories—good‐ and poor‐production years—based on a criteria of fruit density of 50 fruit/m 2 during the bears' hyperphagia periods (Masaki et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…A survey on hard mast productivity between 2006 and 2015 was performed based on masting tree samples from 85 sites (sampling trees: n = 217.5 ± 74.8) (Kozakai et al, 2013;Masaki et al, 2020). The results from that survey were used in the present study to classify the monitored years into two categories-goodand poor-production years-based on a criteria of fruit density of 50 fruit/m 2 during the bears' hyperphagia periods (Masaki et al, 2020). The years 2006The years , 2010The years , 2012The years , and 2014 were categorized as poor-production years, whereas 2007, 2008, 2009, 2011, 2013, and 2015 were categorized as good-production years.…”
Section: Food Availability Datamentioning
confidence: 99%